2002
DOI: 10.1038/sj.bjc.6600584
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of formation of aflatoxin-albumin adducts: a seven-township study in Taiwan

et al.

Abstract: Dietary exposure to aflatoxins is one of the major risk factors for hepatocellular carcinoma. Individual susceptibility to aflatoxin-induced hepatocarcinogenesis may be modulated by both genetic and environmental factors affecting metabolism. A cross-sectional study was performed to evaluate determinants of the formation of aflatoxin covalently bound to albumin (AFB 1 -albumin adducts). A total of 474 subjects who were free of liver cancer and cirrhosis and were initially selected as controls for previous case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
1
19
1
3
Order By: Relevance
“…This is consistent with an earlier observation in Taiwanese (26), in which the detection rate of AAA of males (42.5%) was significantly higher than that of females (21.6%) (OR = 2.6, 95% CI = 1.4-5.0). Nevertheless Chen et al (9) found a significantly higher level of AAA among female Taiwanese adolescents (age 13-15 years) compared with males.…”
Section: Gender Effect On Aaa Levelsupporting
confidence: 94%
“…This is consistent with an earlier observation in Taiwanese (26), in which the detection rate of AAA of males (42.5%) was significantly higher than that of females (21.6%) (OR = 2.6, 95% CI = 1.4-5.0). Nevertheless Chen et al (9) found a significantly higher level of AAA among female Taiwanese adolescents (age 13-15 years) compared with males.…”
Section: Gender Effect On Aaa Levelsupporting
confidence: 94%
“…Notably, when the interaction between aflatoxin exposure and GSTT1 genotype was considered, aflatoxin exposure by itself was not a significant determinant of HCC risk among chronic HBsAg carriers. These results pointed to the importance of gene-environment interactions in HCC development [122,123].…”
Section: Cancer Of the Gastrointestinal Tract And The Livermentioning
confidence: 98%
“…This type of tumour is seen at high frequencies in Southeast Asia and in Subsaharan Africa. In Taiwan, it is the leading cancer in males, and the fifth in females [122,123]. Aetiologically, it has been linked with both viral (hepatitis B/C) and chemical (aflatoxin B 1 ) factors.…”
Section: Cancer Of the Gastrointestinal Tract And The Livermentioning
confidence: 99%
“…5,6 Because the t l/2 of AFB l -albumin adducts in blood is $20-fold longer than that of urinary metabolites ($24 h) such as the AFB l -N 7 -guanine adduct or AFB l -mercapturic acid, albumin adducts have been more often used as a biomarker of AFB l exposure and disease risk. [7][8][9][10][11][12][13] The structure of an aflatoxin adduct formed with lysine in albumin was first elucidated via a proof by synthesis using AFB l dibromide as the starting material. [14][15][16] Condensation of the dialdehyde tautomer of 8,9-dihydro-8,9-dihydroxy-AFB l with the e-amino group of N a -acetyl-lysine to form a Schiff base, followed by an Amadori rearrangement to an a-amino ketone was proposed to lead to the formation of the N a -acetyl-lysine-AFB l adduct over a 24 h period.…”
Section: Introductionmentioning
confidence: 99%